دراسة دلالية للأدب الديني المترجم: أحاديث القتال أنموذجا - Shair Ali Khan (التراث الأدبي)
Sword is a tool of fear when it is in the hands of cruel people showing the inhumanity of human. But when it is in the hands of good tempered people, those who believe in Allah, His last Prophet, and the last day in this universe which is full of civilized and uncivilized cultures, here the reality of humanity comes into light.  Allah created humans with diverse nature, physique, and abilities. Some of them love to serve humans and among them who just want to rule them with cruelty and barbarism killing them, destroying them with various types of punishment. The history reveals these two faces of humanity in the story of two sons of Adam (عليه السلام). That is why Allah sent His messengers to teach, guide and lead humans to the right path, to the justice, and good deeds. The last Prophet Muhammad (صلى الله عليه وسلم) is Arab and the last revelation is in Arabic language which is rhetorically, linguistically and culturally a vast language. Translating this religious literature into other languages is a challenging task due to its complex and vast linguistic nature. The words of our Prophet Muhammad (صلى الله عليه وسلم) should be translated correctly from Arabic into other languages. The word used for fighting in the sayings of Prophet Muhammad (صلى الله عليه وسلم) contain deep meanings that cannot be understood without having a full comprehension of Arabic language and its culture. This study aims to analyze Ahadith as an example of religious literature that contains words of fighting and their translation to explain that Islam invites the humanity to peace.